1998
DOI: 10.1038/sj.onc.1201479
|View full text |Cite
|
Sign up to set email alerts
|

A one centimorgan deletion unit on chromosome Xq12 is commonly lost in borderline and invasive epithelial ovarian tumors

Abstract: We have used polymerase chain reaction (PCR) ampli®cation of tandem repeats to study the pattern of allelic loss on chromosome X11.2-q12 in borderline and invasive epithelial ovarian tumors. Using eight microsatellite markers spanning Xq11.2-q12, 41 borderline and 65 invasive ovarian tumors, together with their corresponding normal tissues, were analysed. The highest percentage of loss of heterozygosity (LOH) was observed at the DXS1194 locus in borderline tumors (four of 16 informative cases, 25%) and at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…Perinchery et al 24 studied the frequency of losses of chromosome Y in prostate cancer and found that loss of the genes analyzed was more frequent in tumors of advanced stage and grade. An additional study of epithelial ovarian tumors showed a high frequency of LOH at the androgen 31 Our finding that PETs tend to show loss of the whole X chromosome suggests that there is no particular selection for a specific region in this tumor type, a finding also supported by the CGH study of Stumpf et al 13 Overall, our study suggests that loss of sex chromosomes in pancreatic endocrine tumors may be associated with features of malignancy and a poorer prognosis. The possibility that these losses could result from a more generalized chromosomal instability or be an effect of aging is not supported by our results.…”
supporting
confidence: 70%
“…Perinchery et al 24 studied the frequency of losses of chromosome Y in prostate cancer and found that loss of the genes analyzed was more frequent in tumors of advanced stage and grade. An additional study of epithelial ovarian tumors showed a high frequency of LOH at the androgen 31 Our finding that PETs tend to show loss of the whole X chromosome suggests that there is no particular selection for a specific region in this tumor type, a finding also supported by the CGH study of Stumpf et al 13 Overall, our study suggests that loss of sex chromosomes in pancreatic endocrine tumors may be associated with features of malignancy and a poorer prognosis. The possibility that these losses could result from a more generalized chromosomal instability or be an effect of aging is not supported by our results.…”
supporting
confidence: 70%
“…Of interest, a 75% rate of loss of heterozygosity at 11q23.3-24.3 that harbors the PR gene locus (44,45) had been reported, and one of us (S.C.M.) recently detected a 40% loss of heterozygosity at Xq11.2-q12 that harbors the AR gene (46). In the present study, we observed significant downregulation of PR and AR mRNA expression in several established ovarian cancer cell lines and in the small number of primary cell cultures established from patients with late serous adenocarcinoma.…”
Section: Fig 2 Sequence Analyses Of the Wild-type Er␣ Transcript (Ementioning
confidence: 99%
“…Reduced DLC-3 mRNA levels could also result from genomic DNA losses. Loss of heterozygosity studies have suggested the presence of one or more tumor suppressor genes on the X chromosome (reviewed in Spatz et al, 2004), and the DLC-3 locus is close to an Xq region commonly lost in ovarian epithelial tumors (Edelson et al, 1998). Generation of DLC-3-specific antibodies will be needed to determine whether DLC-3 expression in tumors is reduced at the protein level and whether this is correlated with changes in mRNA levels.…”
Section: -----------------------------------------------------------Dmentioning
confidence: 99%